2019
DOI: 10.3892/ol.2019.9907
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 as a potential predictive factor for adverse events associated with platinum‑based antitumor agent‑induced peripheral neuropathy

Abstract: Glutathione S-transferase (GST) exhibits antidotal effects on numerous drugs, including platinum-based antineoplastic drugs. Furthermore, GST Pi 1 (GSTP1) polymorphism is associated with peripheral neuropathy. In the present study, it was determined whether GSTP1 can predict adverse events associated with platinum-based antitumor agent-induced peripheral neuropathy among Japanese patients. The subjects included 122 patients, among whom 105 patients had colorectal, 16 had gastric, and one patient had pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This polymorphism results in the reduced activity of the GSTP1 enzyme and loss of this gene's alleles causes the complete loss of enzymatic activity. 85,86 Other studies suggest that polymorphisms at these sites are associated more with changes in PBC toxicity, such as granulocytopenia and peripheral neuropathy induced by platinum. 86,87 Several recent studies showed that the GSTP1 polymorphism represents a predictive factor for the outcome of NSCLC patients treated with PBC 88 ( Table 1).…”
Section: Detoxication Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This polymorphism results in the reduced activity of the GSTP1 enzyme and loss of this gene's alleles causes the complete loss of enzymatic activity. 85,86 Other studies suggest that polymorphisms at these sites are associated more with changes in PBC toxicity, such as granulocytopenia and peripheral neuropathy induced by platinum. 86,87 Several recent studies showed that the GSTP1 polymorphism represents a predictive factor for the outcome of NSCLC patients treated with PBC 88 ( Table 1).…”
Section: Detoxication Processmentioning
confidence: 99%
“…85,86 Other studies suggest that polymorphisms at these sites are associated more with changes in PBC toxicity, such as granulocytopenia and peripheral neuropathy induced by platinum. 86,87 Several recent studies showed that the GSTP1 polymorphism represents a predictive factor for the outcome of NSCLC patients treated with PBC 88 ( Table 1). Data from a meta-analysis showed that the Asian GSTP1 genotype, IIe105Val IIe/Val and Val/Val, exhibited a better response compared with IIe/IIe 89 (Table 1).…”
Section: Detoxication Processmentioning
confidence: 99%
“…The GSTP1 Ile105Val (rs1695, A>G) is a missense mutation and affects the activity of the GSTP1 enzyme. Oxaliplatin-related cumulative peripheral neuropathy was reported to be more frequent and severe in patients with heterozygous (AG) genotype when compared to patients with wild-type alleles (AA) [ 9 ]. Wiese et al [ 10 ] conclude that GSTP1 c.313A>G polymorphism was associated with the overall survival of patients treated with oxaliplatin-based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The GSTP1 Ile105Val (rs1695, A>G) is a missense mutation and affects the activity of the GSTP1 enzyme. Oxaliplatin-related cumulative peripheral neuropathy was reported to be more frequent and severe in patients with heterozygous (AG) genotype when compared to patients with wild type alleles (AA) [6]. Wiese et al [7] conclude that GSTP1 c.313A>G polymorphism was associated with the overall survival of patients treated with oxaliplatin-based therapy.…”
Section: Introductionmentioning
confidence: 99%